ANTIMICROBIAL THERAPY IN TYPHOID - SHULTZ, SELMA; RUIZ SANCHEZ, FRANCISCO; RUIZ SANCHEZ, AMADO; MC DERMOTT, WALSH; KNIGHT, VERNON (CORNELL UNIVERSITY MEDICAL COLLEGE, NEW YORK, NY, EUA, 1950)
A study was made of the effects of k-strophanthoside on the contractions of the gastrocnemius- plantar is muscles made ischemic by intermittent occlusion of the aorta in cats anesthetized with Dial The intraven injn of 01-02 mg/kg of k-strophanthos
ARCH INTERN MED
Keywords: ANTIMICROBIAL, THERAPY, TYPHOID; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MICROBIOLOGIA Y PARASITOLOGIA MEDICAS